Digital Strategies and Policy Challenges in Healthcare and Food Supply Chain Resilience - Lazuardi, Billy; Muharam, Husni (Sinergi International Journal of Logistics, 2024)
In an era of increasingly frequent disruptions such as natural disasters, pandemics, and geopolitical conflicts, the resilience of logistics systems has become a pressing global concern. This narrative review explores how logistics resilience is operationalized and supported across diverse contexts, with a particular focus on digital transformation and cross-sectoral strategies. The review draws upon literature sourced from Scopus, PubMed, and Google Scholar, using targeted keywords to capture studies published within the last five years. The inclusion criteria emphasized peer-reviewed empirical research related to supply chain resilience, healthcare logistics, and food systems. Findings reveal that strategies such as supply chain diversification, decentralized infrastructure, and real-time monitoring via IoT and AI significantly enhance adaptive capacity. Blockchain and big data analytics further improve transparency, accountability, and decision-making speed. However, disparities across regions remain prominent, particularly due to limited infrastructure, policy constraints, and institutional fragmentation. These systemic barriers inhibit the implementation of resilient logistics in low- and middle-income countries. The discussion highlights the importance of context-specific adaptation, regulatory reform, and the alignment of institutional systems with digital innovation. The review concludes by calling for more comparative and interdisciplinary studies to fill empirical gaps and support the development of globally relevant policy and operational frameworks. Strengthening logistics resilience demands integrated strategies that bridge technology, governance, and localized practice.